Abnormal wire's trajectory during edge-to-edge mitral valve repair—a rare case report of inferior vena cava anomaly. Issue 2 (7th February 2022) - Koren, Ofir; Patel, Vivek; Koseki, Keita; Natanzon, Sharon Shalom; Friedman, John; Makkar, Raj R
Abstract: Background: Inferior vena cava (IVC) anomalies are rare and diagnosed incidentally as most patients are asymptomatic. We present a case where an abnormal course of the wire during percutaneous mitral valve repair revealed abnormal IVC anatomy leading to procedure termination. We summarized all IVC anomalies relevant to cardiovascular physicians and designed a simplified tool to illustrate their course for differential diagnosis. Case summary: A 78-year-old female presented with severe and symptomatic mitral regurgitation. The heart team decided to proceed with a percutaneous option, considering the patient's high surgical risk. While ascending from the femoral vein, the wire took an abnormal course to the left side of the vertebrae and continued beyond the cardiac silhouette downwards the right atrium (RA). We decided to abort the procedure due to the high risk for vascular complications assuming the need to cross it with the device's delivery system. Retrospective computed tomography analysis revealed an interrupted IVC at the level of the renal vasculature and azygos continuation toward the RA via a dilated superior vena cava. The patient was referred to surgery and had successful mitral and tricuspid valve repair and was discharged home in good health. Discussion: The increased number of minimally invasive percutaneous procedures, especially for valvular heart disease, mandates a profound understanding of the arterial, and venous system anatomy. Inferior vena cava anomalies represent a group of anomalies with different paths and variations and have a tremendous impact on all aspects of the procedure.